Increasing the Bearing Capacity of Shallow Foundations on Soft Soil After the Installation of Micro-Piles - Isnaniati; Mochtar, Indrasurya B. (Journal of the Civil Engineering Forum, 2023)
The bearing capacity of shallow foundations on soft soils can generally be estimated based on Local Shear Failure (Terzaghi theory). Several researchers previously stated that the installation of micro-piles on the failure area (slide) can increase the shear strength of the soil. This can be followed up by providing micro-pile reinforcement to prevent lateral soil movement. Therefore, this research was conducted to increase the bearing capacity of shallow foundations on medium-consistency soft clay soils that have been reinforced with micro piles. The research was conducted using modeling in the laboratory with a scale of 1:30. The soil sample used was kaolin clay made from slurry made from kaolin powder with a water content (wc = 1.77 LL), liquid limit (LL = 62.35%) and sample diameter (d = 33 cm). The slurry was formed by compacting at a medium consistency level with an undrained cohesion value (cu = 0.397 kg cm-2). The micro-pile material in the form of apus bamboo was installed, varying in diameter (d) 0.2 cm (0.027 B), 0.3 cm (0.04 B), and 0.5 cm (0.07 B); sum (n) 4, 9, 16, and 25; and length (L) 10 cm (1.33B), 13 cm (1.73B), and 16 cm (2.13B) micro-piles. While the foundation model uses a squarefoundation B x B with B = 7.5 cm. The tests were carried out before and after the micro-piles were reinforced with a soil shear failure test. The results showed that a decrease of 0.1B caused an increase in the ultimate bearing capacity of the micro-pile (qult-empirical, 0.1B) from the ultimate bearing capacity before installing the micro-pile. This value is then used to determine the ultimate bearing capacity ratio so that Rq,0.1B = qult-empirical,0.1B/qult-Terzaghi with the optimum bearing capacity ratio occurring at Rq,0.1B with n3 = 16, d2 = 0.04B, L2 = 1.73B.